2012
DOI: 10.1088/0268-1242/27/5/055014
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and temperature distribution in semiconductors

Abstract: The temperature distribution in the homogeneous bipolar semiconductor, when the electrical current flows through it, is investigated. The case of the linear approximation with respect to an electrical current is considered. The presence of nonequilibrium charge carriers as well as the processes of recombination is taken into account. It is shown that the temperature distribution in a bipolar semiconductor in a one-dimensional case is a linear function of a coordinate under both small and strong recombinations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This enhancement is a direct consequence of the sample displacement along the heat propagation axis, such that larger displacements are obtained for the thinner substrate (30 m). This is reasonable as the displacement of a two-layer sample is inversely proportional to the (thickness) 3 of the substrate. Based on the analysis of the photogenerated carrier densities and temperature differences at the illuminated and nonilluminated sides of the samples, for three characteristic modulation frequencies, it has been shown that the displacement of two-layer samples is larger than that of the single-layer ones.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This enhancement is a direct consequence of the sample displacement along the heat propagation axis, such that larger displacements are obtained for the thinner substrate (30 m). This is reasonable as the displacement of a two-layer sample is inversely proportional to the (thickness) 3 of the substrate. Based on the analysis of the photogenerated carrier densities and temperature differences at the illuminated and nonilluminated sides of the samples, for three characteristic modulation frequencies, it has been shown that the displacement of two-layer samples is larger than that of the single-layer ones.…”
Section: Discussionmentioning
confidence: 74%
“…It is well known that the illumination of semiconductors with a modulated light source can generate charge carriers that cause different types of thermal responses [1][2][3][4][5]. There are various spectroscopic methods within photothermal sciences that can be used to analyze such thermal responses [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 These pairs are called photogenerated or excess carriers, their density takes its highest value at the illuminated surface, where the majority of light is absorbed, 2,3 and, therefore, they induce various effects in semiconductors. [4][5][6] Photogenerated excess carriers can change the heat transport dynamics and temperature profiles inside semiconductors. [7][8][9][10][11][12][13] In photoacoustics (PA), for instance, some theoretical studies showed that the number of photogenerated excess carriers generated in both n-and p-type semiconductors illuminated with a modulated light source increases with the light absorption, and they are able to significantly change the temperature distribution at the surface and inside the materials.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of PA and PT methods can be used to characterize the semiconductors in details [14][15][16][17]. The temperature changes can be detected measuring directly a sample surface temperature variations or perturbations of temperature-dependent thermodynamic parameters, such as pressure or density.…”
Section: Introductionmentioning
confidence: 99%